PEMASARAN KOTA SEBAGAI PENDEKATAN DALAM PERENCANAAN RUANG KOTA - Prihantoro, Feri (VITASPHERE, 2012)
City marketing is a strategy to achieve city s vision, it should be supported with city planning as a foundation for city to create image, attraction, sufficient infrastructure, and human resources which support city marketing. City planning ;s not only to supply the citizen, but it is also to satisfy market target. In Indonesia, city planning process refers to guidance which is produced by central government. This situation makes city planning product is